7 Modified immune cell therapy ameliorates murine lupus nephritis and induces regulatory cell subsets. (April 2019) - Speer, Claudius; Kim, Daniela; Kleist, Christian; Morath, Christian; Schmitt, Anita; Schmitt, Michael; Sommerer, Claudia; Steinborn, Andrea; Kälble, Florian; Nusshag, Christian; Wang, Lei; Kunz, Alexander; et al.
Abstract : Background: Modified immune cells (MICs) are mononuclear cells that gain immunosuppressive properties after incubation with the proliferation inhibitor mitomycin C. We showed that syngeneic MIC cell therapy prevented experimental autoimmune encephalitis (EAE) as well as alloreactive rejection in rat heart and hindlimb and pig kidney transplantation. We now aimed to translate these encouraging investigations to prevent murine lupus nephritis and control autoimmunity by MIC therapy. Methods: Splenocytes of syngeneic NZB/W F1 (BWF1) mice were harvested from a donor, incubated with mitomycin C and injected into recipients tail vein after matching for age and disease activity. Group 1 received no MIC therapy, group 2 standard-dose MIC therapy with 1.5 × 108/kg BW once and group 3 repeated MIC therapy with 1.5 × 108/kg BW at week 1, 2 and 3, respectively. Group 4 was dosed with repeated MIC therapy before disease onset as preemptive treatment approach. Disease activity was monitored by loss of body weight, protein excretion and serum creatinine. Combined primary endpoint was day 40 post-treatment, protein excretion 3 g/L for 2 consecutive weeks and >30% loss of original body weight. Histopathology with PAS and HE staining was performed to assess degree of lupus nephritis. In the peripheral blood we determined regulatory cell subsets. Results: MIC therapy prevented the progression of fatal lupus nephritis in BMF1 mice. Protein excretion and serum creatinine were lower in standard-dose group and preemptive group compared to control group whereas repeated MIC therapy in active disease failed to inhibit both significantly. Accomplishment of combined primary endpoint was significantly increased in group 1 (67%) compared to group 2 (14%), group 3 (14%) and group 4 (0%), respectively. Renal architecture was preserved throughout different MIC treatment groups with decreased glomerular and tubular damage scores. After MIC therapy, frequencies of CD8 +CD25+FoxP3+regulatory T cells and CD19 +CD5+CD1 dhigh regulatory B cells increased significantly, whereas double negative T cells were markedly reduced throughout all treatment groups. Conclusions: MIC therapy inhibits progression of active lupus nephritis. Interestingly, preemptive MIC therapy was even able to prevent onset of disease since no significant disease activity was observed at completion of the study. In accordance with our previous pre-clinical EAE experiments and a first in-human clinical trial in living-donor kidney transplantation (TOL-1 study), MIC therapy enables an in-vivo induction of regulatory cell subsets. This clinically applicable cell therapeutic approach may control lupus nephritis by specifically silencing deleterious autoimmune response. Funding Source(s): Research grant from TolerogenixX GmbH Disease activity was assessed after MIC cell therapy by loss of original body weight (A), protein excretion via semiquantitative sticks (B), albuminuria via ELISA (C) and serum creatinine via ELISA (D). Primary endpoint was defined as day 40 post-treatment, protein excretion 3 g/L for 2 consecutive weeks and >30% loss of original body weight (E). Histopathology with PAS and HE staining was performed. Representative PAS staining for different treatment groups and the control group are shown (F). Different regulatory cell subsets as well as DN T cells were determined in peripheral blood. Representative dot plots of regulatory CD19 +CD5+CD1 dhigh B cells, CD8 +CD25+FoxP3+T cells and CD3 +CD4 CD8- double-negative T cells are shown (G).